OBJN mourns a nurse leader: Haydée Guanaes Dourado, PhD - Cruz, Isabel (Online Brazilian Journal of Nursing, 2005)
The nursing community recently lost a prominent member in the death of Haydée Guanaes Dourado, who died April 10. Dr Haydée Guanaes Dourado was the first director of the Nursing School at Bahia Federal University. She contributed strongly to the Brazilian Nursing Association and its journal. She was active throughout her career and a leadership in the ethical and legislative issues related to creation of the National Nursing Board and the Professional Nursing Act. The OBJN knows that her contributions and impact on the nursing profession will maintain alive the Haydée Guanaes Dourado ́s memory.